Trends in the Use of Artificial Intelligence in Science Education: Bibliometric & Biblioshiny Analysis (1975-2024) - Ayuni, Rizki Tika; Jaedun, Amat; Zafrullah, Zafrullah; Ramadhani, Atika Miftah (Postgraduate, University of Mataram, 2024)
This research was conducted to look at research trends in the Scopus database regarding the study of Artificial Intelligence in Science Education. Using the PRISMA method, researchers selected and determined 146 documents that were ready to be analyzed using bibliometric and biblioshiny methods with the help of the R program and Vosviewer. From the results of the analysis carried out, it was concluded that research on Artificial Intelligence in Science Education in the Scopus Database started from 1975 to 2024, with an 8-fold increase in the number of publications, and 13 times the number of citations in the last 7 years. China was the country with the highest contribution to this research, showing 17(11.64%) publications and 418(13.65%) citations.